Effective implementation of the microblowing technique on airfoils - Zohary, Aideal Czar (Kulliyyah of Engineering, International Islamic University Malaysia, 2021)
The Micro Blowing Technique (MBT) which has been proven by NASA to reduce skin friction drag on a flat plate by up to 70 to 80 percent in the subsonic speed regime, outperforms the conventional blowing by means of adopting micro holes to ensure the introduction of minimal effective roughness. Past researchers have failed to effectively apply MBT on airfoils. The aim of this study is to ensure reduction in both components of drag on an airfoil in subsonic flows through investigating proper selection of airfoils and strategic blowing placement. Based on a detailed in-depth analysis of their work and reasons for earlier failures, a conclusion has been reached that MBT performs well on concave pressure-recovery type of airfoils when positioned in the positive pressure drag region on the lower surface near the trailing edge. The S1223 airfoil that has a sufficient extent of this region while featuring high-lift properties and mild stall characteristics makes it an excellent candidate for effective MBT applications and UAV design. Demonstrated evidence through numerical investigation showed that a proper implementation of MBT on a S1223 airfoil improves its lift-to drag ratio by 30%. A simple and effective CFD modelling of MBT on a Clark Y airfoil shows trends similar to published experimental data involving hot wire and wake pressure measurements. Results consist of the effect of Reynolds number, blowing fraction and contribution of individual drag components to aid understanding on how MBT influences the overall flow and drag. The CFD results are also validated against XFOIL. The findings indicate that total drag reduction is heavily dependent in the manner in which MBT affects the pressure distribution around the airfoil. A proper selection of the region in which micro blowing is located will lead to a significant reduction in pressure drag. At a Reynolds number of 0.3 x 106, drop in skin friction drag reached almost 5% while reduction in pressure drag is about 37.5% across a range of angles of attack when having MBT applied at 0.68-0.80 x/c. It is concluded that the integration of properly located MBT on concave pressure-recovery type of airfoils should produce significant improvement in their performance.